Orphan Drug Dynamics in India: Challenges, Strategies, and Success Story - Patel, Megha (Asian Journal of Pharmaceutics (AJP), 2024)
An orphan drug is the pharmaceutical product formulated to treat rare health conditions. This article provides a comprehensive overview of orphan drugs, focusing on their definition, regulatory status, as well as the challenges and initiatives related to orphan drug development and accessibility in India. It highlights the significant improvements in India’s regulatory framework for orphan drugs, including expedited review processes and exemptions from certain clinical trial requirements. The article also presents a list of orphan drugs sponsored by Indian companies, demonstrating India’s contributions to orphan drug development. Furthermore, it showcases a success story of an orphan drug introduced by Sun Pharmaceutical Industries Limited, emphasizing the importance of research and innovation in addressing unmet medical needs. Finally, future directions in orphan drug research, such as gene therapy and repurposing existing drugs, are discussed, along with the potential of global collaboration and regulatory harmonization to expedite access to innovative therapies for patients worldwide